1996
DOI: 10.1097/00000478-199612000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Vascular Tumors of the Serous Membranes Mimicking Mesothelioma

Abstract: Malignant endothelial neoplasms involving the serous membranes are rare, and only a few cases have been documented. We report 14 patients with epithelioid hemangioendothelioma (EHE) or epithelioid angiosarcoma (EA) diffusely involving the pleural, peritoneal, or pericardial cavities, resulting in a picture closely resembling mesothelioma. The mean age at diagnosis was 52 (range, 34-85). The patients included two women and one man with peritoneal tumors, eight men with pleural tumors, and three men with pericar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(109 citation statements)
references
References 25 publications
1
107
1
Order By: Relevance
“…The expression of von Willebrand factor and CD34 has not been reported in malignant mesothelioma and the results of this study support previous investigations. 8 The present study indicates no definite immunohistochemical evidence of vascular diVerentiation in any of the cohort of 92 malignant mesotheliomas studied and we conclude that vascular marker expression (and endothelial diVerentiation) does not occur or is a very infrequent finding in malignant mesothelioma. The use of a combination of the vascular markers CD31 and CD34 would therefore allow eVective distinction of malignant mesothelioma from epithelioid angiosarcoma.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The expression of von Willebrand factor and CD34 has not been reported in malignant mesothelioma and the results of this study support previous investigations. 8 The present study indicates no definite immunohistochemical evidence of vascular diVerentiation in any of the cohort of 92 malignant mesotheliomas studied and we conclude that vascular marker expression (and endothelial diVerentiation) does not occur or is a very infrequent finding in malignant mesothelioma. The use of a combination of the vascular markers CD31 and CD34 would therefore allow eVective distinction of malignant mesothelioma from epithelioid angiosarcoma.…”
Section: Discussioncontrasting
confidence: 66%
“…5 It has been described as originating from the pleura 6 and peritoneum. 7 In the pleura the main diVerential diagnosis is that of diVuse malignant mesothelioma 8 and clinicopathological distinction can be problematical. Firstly, a diVuse serosal growth pattern is a characteristic feature of malignant mesothelioma but this "mesotheliomatous" pattern is not specific and has been recognised in some non-mesothelial tumours, most notably carcinomas and, very rarely, sarcomas including epithelioid haemangioendothelioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two sarcomas with the greatest potential of being confused with pleomorphic mesotheliomas are angiosarcomas and the pleomorphic variant of malignant fibrous histiocytoma. Pleural angiosarcomas are often epithelioid and can easily be mistaken for a mesothelioma, both clinically and histologically, [27][28][29][30] and examples of epithelioid pleural angiosarcomas exhibiting marked pleomorphism that could easily be confused with pleomorphic mesotheliomas have been documented in the literature. 31 The pleural biopsy of one of the mesotheliomas cases in this study (case 1), in addition to being somewhat hemorrhagic, showed areas in which the neoplastic cells appeared to be lining irregular spaces resembling the vascular spaces seen in an angiosarcoma ( Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelioid hemangioendothelioma and epithelioid angiosarcoma may mimic epithelioid MM by clinical presentation, radiologic features, and morphology. [19][20][21] It has been recommended that a vascular tumor should be suspected in the presence of abortive vessel formation and in the absence or low-level expression of cytokeratin and mesothelial markers, such as calretinin, and confirmed with 2 or more vascular markers. 19,20 It is noteworthy that sarcomas and thymoma may be, at least to some extent, positive for mesothelial markers.…”
Section: Differential Diagnosis Between Epithelioid MMmentioning
confidence: 99%